2020
DOI: 10.1126/scirobotics.aay6626
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose–derived mesenchymal stem cell–based medical microrobot system for knee cartilage regeneration in vivo

Abstract: Targeted cell delivery by a magnetically actuated microrobot with a porous structure is a promising technique to enhance the low targeting efficiency of mesenchymal stem cell (MSC) in tissue regeneration. However, the relevant research performed to date is only in its proof-of-concept stage. To use the microrobot in a clinical stage, biocompatibility and biodegradation materials should be considered in the microrobot, and its efficacy needs to be verified using an in vivo model. In this study, we propose a hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(142 citation statements)
references
References 50 publications
2
140
0
Order By: Relevance
“…Once in there, a permanent magnet was used to hold in place the cell loaded microrobots facilitating the adhesion and proliferation of the stem cells in the target location. [231] Microrobots have also been used to transport individual cells without functioning as a scaffold, but rather by using chemical interactions or physical stimulation. Different types of blood cells have been coupled with motile robots to take advantage of their biological function.…”
Section: Living Cellsmentioning
confidence: 99%
“…Once in there, a permanent magnet was used to hold in place the cell loaded microrobots facilitating the adhesion and proliferation of the stem cells in the target location. [231] Microrobots have also been used to transport individual cells without functioning as a scaffold, but rather by using chemical interactions or physical stimulation. Different types of blood cells have been coupled with motile robots to take advantage of their biological function.…”
Section: Living Cellsmentioning
confidence: 99%
“…However, in such a transport process, cell viability may be affected by fluid shear force and magnetic field. Cells loaded micro/nanorobot was also applied in knee cartilage regeneration in vivo [88]. The human adipose-derived MSCs (hADMSCs)-located microrobot could move to the lesion of rabbit knee cartilage under the guidance of magnetic field.…”
Section: Application Of Drug-loaded Micro/nanorobots In Vivomentioning
confidence: 99%
“…The required magnitude of the magnetic field is determined by considering the size of the MCTAC and the region of interest (ROI). Although the proposed method can be applied to an MCTAC containing agents such as stem cells [25], doxorubicin [26], macrophages [27], ferumoxytol [28], and a multifunctional nanorobot [1], this study uses stem cells as a therapeutic agent for cartilage repair in order to validate the proposed method. Here, the required magnetic field intensity is assumed to be a minimum of 40 mT, based on previous studies on magnetically actuated micro-scaffolding containing MSCs and a magnetoresponsive stem cell spheroid [12,13].…”
Section: Fixation Mechanismmentioning
confidence: 99%
“…Therefore, to achieve external wireless active actuation, an electromagnetic system was incorporated into the MCTAC based on previous microrobot motion control technology [2,23,24]. As a promising result of the combination of the EMA and the MCTAC, Go et al were able to develop a biodegradable scaffold with a porous structure carrying MSCs [25]. Similarly, Yoo et al demonstrated a magnetoresponsive stem cell spheroid-based cartilage recovery platform that enabled precise targeting using magnetic control and low-frequency electromagnetic fields [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation